Waiting rooms of architecture : Malgorzata Maria Olchowska. - Ionescu, Vlad, 1978-; De Caigny, Sofie, 1977-; Exhibition. Antwerpen. Red Star Line Museum (Antwerpen : Vlaams Architectuurinstituut, 2023)
What precedes architecture? Architect and artist Malgorzata Maria Olchowska (° Bartoszyce, 1982) explores how personal and collective memories influence our view of the built environment. The book is built around a text by Vlad Ionescu (Faculty of Architecture and Art, PXL/UHasselt) in which he reflects on the work of Malgorzata Maria Olchowska, from 2009 to today. This is supplemented and illustrated by means of a visual essay in which Olchowska shows her work of the last five years. The design of the book is done by Ward Heirwegh. "There is the house we design as an adult, the one we drew as a child, the property of the vir probatus, the house that provides safety and the one that frightens the child. Olchowska's prints work with these imaginary alterations as façades or as side and interior views: they are the waiting rooms of architecture." Vlad Ionescu. Exhibition: Red Star Line Museum, Antwerp, Belgium (31.03. - 23.04.2023).
The modelling of architecture Ionescu, Vlad
31/03/2023 - 23/04/2023
boek
Keywords: Olchowska, Malgorzata Maria, -- 1982-.; Olchowska, Malgorzata Maria; Exhibitions